If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9t + -3s = 2 Reorder the terms: -3s + 9t = 2 Solving -3s + 9t = 2 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-9t' to each side of the equation. -3s + 9t + -9t = 2 + -9t Combine like terms: 9t + -9t = 0 -3s + 0 = 2 + -9t -3s = 2 + -9t Divide each side by '-3'. s = -0.6666666667 + 3t Simplifying s = -0.6666666667 + 3t
| -1-8(3b+5)=-113 | | 9(p-4)=4 | | (x*1.5*20)+(x*40)=600 | | 3s-9t=1 | | 6+6d=-6+10d | | b^4-2500b^2+1440000=0 | | -3(2x-2)=-2+3x | | b^2-2500b^2+1440000=0 | | -1+2g+2=6 | | -17.5+15y=10 | | 12+2n=7+2n+3 | | 34-x=57-42 | | 4x+n=100 | | 10x-4+5x+79=180 | | 9x-3=2x-15 | | 5q+10=-10+10q+5 | | 2(3k+58)=4(k+810) | | (4+5x)(4-5x)= | | 17x+2y=0 | | 4x+(4x-3)=37+3x | | 3(4z+900)=7(z+10100) | | (6x)(x+3)=0 | | 4(2p-8)-6=20+4(p+6) | | -6w+1=9-4w | | -10f+10=-12f | | -v=2v+9 | | s=120+71 | | x+(x*.15)=805 | | -7z-8=-8z | | -(8x-4)=-4x-3(x-3) | | 15.16+13.5k=-4.86+12.1k | | 15000/3= |